Optimasi Kontrol Katup Aliran Debit Air Pada Mikro-Hidro Berbasis Ant Colony Optimization - Asnun Parwanti; Markhaban Siswanto; Cholil Hasyim; Mohammad Hasib Al Isbilly (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2018)
Technically, Microhydro has three main components in generation, namely water (as an energy source), turbine, and generator. Water flowing with a certain capacity is channeled to the height of a certain house (turbine house). Water discharge is regulated by a water discharge regulating valve. In a power house, the water installation will pound the turbine, the turbine will receive energy directly from the water and turn it into mechanical energy. The shaft is then transmitted to the generator using a clutch. Because of frequent fluctuations in the frequency and voltage of the system which can cause damage to electrical equipment. Therefore optimization of the water flow valve control is used so that the frequency control can be more stable. To obtain optimal control parameters on a micro hydroelectric power generation system, the Ant Colony Optimization (ACO) method is used. The results of this study will be tried by other methods, the results of which may be better.